Edge‐Site‐Rich Ordered Macroporous BiOCl Triggers CO Activation for Efficient CO2 Photoreduction. Issue 6 (1st December 2021) - Liu, Gaopeng; Wang, Bin; Zhu, Xingwang; Ding, Penghui; Zhao, Junze; Li, Huaming; Chen, Ziran; Zhu, Wenshuai; Xia, Jiexiang
Abstract: Endowing a semiconductor with tunable edge active sites will effectively enhance catalytic performance. Herein, an edge‐site‐rich ordered macroporous BiOCl (BiOCl‐P) with abundant dangling bonds is constructed via the colloidal crystal template method. The edge‐site‐rich ordered macroporous structure provides abundant adsorption sites for CO2 molecules, as well as forms numerous localized electron enrichment areas, accelerating charge transfer. DFT calculations reveal that the dangling bonds‐rich configuration can effectively reduce the CO2 activation energy barrier, boost the CO double bond dissociation, and facilitate the proton electron coupling reaction. As a result, the BiOCl‐P achieves a higher CO and CH4 generation rate of 78.07 and 3.03 µmol g −1 under 4 h Xe lamp irradiation in a solid–gas system. Finally, the CO2 molecules′ conversion process is further investigated by in situ Fourier‐transform infrared spectroscopy. This work realizes a new avenue toward the design of vibrant semiconductors on the nanoscale to boost inert CO2 photoreduction. Abstract : An edge‐site‐rich ordered macroporous BiOCl is constructed via the colloidal crystal template method. Notably, the CO2 adsorption/activation and photoexcited carriers transfer performance can be enhanced simultaneously in this system, achieving an efficient CO2 photoreduction to CO and CH4 .